Effect of polypropylene fiber addition on mechanical properties of concrete based on portland cement - Małek, Marcin; Życiński, Wojciech; Jackowski, Mateusz; Wachowski, Marcin (Technical Sciences, 2018)
In this work results of poly(propylene) fibers (PP), from recycling process, added into concrete mixture based on portland cement was characterized. The main purpose of this research was to identify direct influence of the fibers addition on the concrete mechanical strength. The recipe of the concrete was prepared using three types of aggregates with different grain size: 0.125–0.250, 0.250–0.500 and 0.500–1.000 mm, deflocculant based on polycarboxylates, water and portland cement (42.5 MPa). To identify structures of the researched samples and fibers light microscopy (LM) observation was performed. Basic properties of concrete mixture were defined by slump cone test and setting time. Mechanical properties such as compressive strength and bending test after 1, 7, 14 and 28 days were characterized. Obtained results were compared with mixtures without fibers modifications. Study was proven that all chosen fibers from recycled origin revealed increased effect on final mechanical properties of concrete and are very perspective for future application in concrete technology.